2022
DOI: 10.2147/idr.s377657
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Retrospective Study of 746 Cases with Maxillofacial Space Infection in Western China

Abstract: Purpose To grasp the current epidemiological situation of maxillofacial space infection and investigate the risk factors contributing to the longer hospitalization of odontogenic space infection in western China. Patients and Methods This retrospective study collected the clinical characteristics from 746 hospitalized patients with maxillofacial space infection and investigated the risk factors associated with longer hospitalization. Pearson’s chi-square test and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Among them, lesion debridement is the primary treatment [ 6 ]. The cause of the disease is mostly caused by a mixed infection of aerobic and anaerobic bacteria [ 7 ], of which Staphylococcus aureus and hemolytic streptococcus are the most common pathogens [ 8 ]. Antibiotics are essential adjuvant therapy during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, lesion debridement is the primary treatment [ 6 ]. The cause of the disease is mostly caused by a mixed infection of aerobic and anaerobic bacteria [ 7 ], of which Staphylococcus aureus and hemolytic streptococcus are the most common pathogens [ 8 ]. Antibiotics are essential adjuvant therapy during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on MFSI have reported various risk factors and profiles of patients [ 4 , 6 13 ]. Literature on the association predictors of length of hospital stay in MFSI is scant [ 7 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study from the United States reported 61,439 hospitalisations attributed to dental infections with 2.96 days mean length of hospital stay and 66 deaths [ 14 ]. The cost of dental infection to humans in the form of serious morbidities and mortalities and potentially preventable hospitalisation is evident across the globe [ 8 , 9 , 11 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%